Muscle fibre typology as a novel risk factor for Hamstring strain injuries in professional football (soccer): a prospective cohort study - Lievens, E.; Van Vossel, K.; Van de Casteele, F.; Wezenbeek, E.; Deprez, D.; Matthys, S.; De Winne, B.; McNally, S.; De Graaf, W.; Murdoch, J. B.; Bourgois, J. G.; Witvrouw, E.; et al. (Sports Medicine, 2022)
Background: Hamstring strain injuries (HSI) are prevalent in team sports and occur frequently in the later phase of matches. In the search for interindividual factors that determine muscle fatigue and possibly injury risk, muscle fibre typology is a likely candidate. Objective: The aim of the study was to determine whether muscle fibre typology is a risk factor for HSI. Methods: A prospective cohort study was conducted over three seasons in professional football players competing in the Belgian Jupiler Pro League (n = 118) and in the English Premier League (n = 47). A total of 27 HSI were sustained during this period. Muscle fibre typology was non-invasively estimated using proton magnetic resonance spectroscopy and was characterized as a fast, slow, or intermediate typology based on the carnosine concentration in the soleus. A multivariate Cox model was used to identify risk factors for HSI. Results: Football players exhibited a wide variety of muscle typologies (slow 44.9%, intermediate 39.8%, fast 15.3%). In the combined cohort, players with a fast typology displayed a 5.3-fold (95% confidence interval [CI] 1.92-14.8; P = 0.001) higher risk of sustaining an index HSI than slow typology players. This was also independently observed in both leagues separately as, respectively, a 6.7-fold (95% CI 1.3-34.1; P = 0.023) and a 5.1-fold (95% CI 1.2-20.4; P = 0.023) higher chance was found in fast typology players than in slow typology players of the Jupiler Pro League and the Premier League cohort. Conclusion: We identified muscle fibre typology as a novel and potent risk factor for HSI in team sports.